i-PRESTIGE : 2022 Annual Report Research, Industrial Linkages and Alumni Division UiTM Cawangan Johor. - Misman, Faridah Najuna; Ismail, Mazida; Mokhtar, Nurkhairany Amyra; Mat Kamal, Siti Nuur-Ila; Majid, Muhammad; Mazan, Diana'; Mohamad Khalid, Rusnani; Md Isa@Kamarudin, Maizura; Abd Aziz, Noreen Noor; Bachok, Mohd Fairuz; Md Isa, Kamariah; Misnan, Mohamad Farid; et al. (Research, Industrial Linkages and Alumni Division, 2022)
In the name of Allah, the Most Gracious and the Most Merciful. May he grant blessing and peace to Prophet Muhammad (S.A.W) and his family. A lot of activities, programs and projects were successfully conducted by our UiTM Cawangan Johor’s academic staff in the year of 2022. Hence, to commemorate these achievements, UiTM Cawangan Johor utilises our yearly i-PRESTIGE to compile and publish all the reports from the different units under the Research, Industrial Linkages and Alumni (PJI&A) Division of UiTM Cawangan Johor. All praise to be to Allah for we have managed to publish the fifth Intellectual Prestige (iPRESTIGE) for the year 2022. Similar to our previous publications, it highlights the success and achievement of PJI&A of UiTMCJ in relation to researches, publications, consultancy projects, innovations, entrepreneurship, community service and alumni activities. May this report inspire more ideas and interests, and spark greater motivations, in the academia and upon other staff, for a more successful and productive year 2023. Last but not least, I would like to congratulate the PJI&A team for successfully putting together the i-PRESTIGE 2022. Your boundless energy and admirable commitment are much appreciated. Thank you to all the other i-PRESTIGE 2022 committee members as well, for your hard work and diligence in ensuring the success of this publication.